Whole genome sequencing reveals novel resistance-conferring mutations and large genome deletions in drug-resistant Mycobacterium tuberculosis isolates from Indonesia - Aung, Htin Lin; Chaidir, Lidya; Pitaloka, Dian Ayu Eka; Miyahara, Yugen; Kumar, Narender; Soeroto, Arto Yuwono; Cook, Greg M; van Crevel, Reinout; Alisjahbana, Bachti; Peacock, Sharon J.; Hill, Philip C (Journal of Global Antimicrobial Resistance, 2025)
•Novel mutations were identified in drug-resistant M. tuberculosis isolates in Indonesia.•Large genome deletions conferring isoniazid resistance were also identified.•Pre-existing mutations resistant to new and repurposed oral drugs were not detected. This study evaluated drug resistance profiles of Mycobacterium tuberculosis (Mtb) isolates in West Java, Indonesia through phenotypic and genomic approaches. We performed phenotypic drug-susceptibility testing (DST), coupled with whole-genome sequencing (WGS) of 142 Mtb isolates identified as RIF-R (Rifampicin resistant) using the Xpert MTB/RIF platform. We found 107/142 (75%) isolates had high-level isoniazid resistance (INH-R) and rifampicin resistance (RIF-R). Of 107 isolates, we found two had novel katG mutations and three had large genome deletions encompassing the katG gene conferring INH-R. We also did not detect pre-existing mutations resistant to new and repurposed oral drugs bedaquiline (BDQ), pretomanid (Pa) and linezolid (LZD). Known drug-resistance conferring mutations reported in this study can be detected by the newly launched Xpert MTB/XDR together with Xpert MTB/RIF, providing clinicians with an expanded drug-susceptibility report without the need for culturing and WGS. On the other hand,the novel mutations and deletions found in this study are escaping routine diagnostics and could drive outbreaks of MDR-TB in Indonesia. The mass rollout of new and repurposed drugs for the treatment of drug-resistant TB in Indonesia is reassured by the absence of pre-existing mutations in this study. However, tools for rapid detection of resistance to these new drugs are urgently required to circumvent treatment-emergent resistance.